Profiles and analysis of cash flows in enterprises: on the example of an enterprise in Kazakhstan and Turkey - Nurzhanova, I.S.; Banu Başar, A. (BUKETOV BUSINESS REVIEW, 2024)
Object: The aim of this research is to conduct a comparative analysis of the cash flow statements of the largest air lines in Turkey and Kazakhstan over the period 2019–2023, using the cash flow dependent activity model. Methods: The study utilized the cash flow transaction model proposed by Gup et al., which serves as a complementary model for estimating financial data derived from cash flow statements. Findings: The article discusses the cash flow statement, its significance, presentation, and reporting, as well as the definition of a business model on which cash flows depend and an explanation of eight different models. It also analyz es the cash flow statements of some of the largest airlines in Turkey and Kazakhstan over the period 2019–2023 and presents the results. Based on the analysis, it concludes that the airlines under study fit the profile of Model 2, indicating a successful business model. Conclusions: When analysed, it is evident that the cash flows of the companies in the study primarily follow Model 2 (+, -, -), which is recognised as the most successful business model. The cash flow profile of successful businesses (+, -, -) ranks first in this study, as it does in all other studies.